Islamic Education in Christian Basic Schools in Iraqi Kurdistan Region - Bestun Omer Ali Surchi; Iyad M. Eid; Nurazzura Mohamad Diah (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
This essay highlights the distinctive educational environment in which different religious affiliations coexist by examining Islamic teaching within Christian schools in Erbil, Iraqi Kurdistan Region. Examine policies and practices that permit the teaching of both Islam and Christianity in Christian schools, fostering an environment of tolerance and respect for students of many faiths. The Paper employs qualitative techniques, such as in-depth interviews with stakeholders, to reveal the obstacles and achievements of this instructional paradigm. The findings show that Islamic education and the cohabitation of Christian and Muslim pupils promote moral growth and social cohesiveness, which in turn promotes a tranquil and harmonious community. The paper highlights how Christian schools can adapt as models for interfaith discourse and Islam in particular.